Hubungan Pengetahuan Ibu Hamil Tentang Buku Kia dengan Persiapan Persalinan di Puskesmas Mamajang Makassar - St Subriani; Samsiah Samsiah; Alamsyah Alamsyah (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: The Maternal and Child Health (MCH) Book plays an essential role in enhancing pregnant women's knowledge of pregnancy health and labor preparation. However, its utilization remains suboptimal, which may affect a mother's readiness for childbirth. Objective: This study aims to analyze the relationship between pregnant women's knowledge of the MCH Book and their birth preparedness at the Mamajang Health Center in Makassar in 2025. Method: This research employs a quantitative design using purposive sampling with 86 pregnant women as respondents. Data were collected using a knowledge questionnaire about the MCH Book and a birth preparedness questionnaire. Data analysis was conducted using the Chi-Square statistical test. Results: The majority of pregnant women demonstrated good knowledge of the MCH Book (75.6%) and were categorized as prepared for childbirth (70.9%). Statistical testing indicated a significant relationship between pregnant women's knowledge of the MCH Book and their birth preparedness (p = 0.001). Conclusion: There is a significant relationship between pregnant women's knowledge of the MCH Book and their birth preparedness at the Mamajang Health Center in Makassar. Health workers are expected to enhance education and optimization of MCH Book utilization to support birth preparedness.